Chest pain in a young patient: an unusual complication of Epstein-Barr virus - Raman, Lavanya (BMJ Publishing Group, 2014)
A 29-year-old man presented with sudden left-sided pleuritic chest pain on a background of sore throat during the preceding week. On examination he had tender cervical lymphadenopathy, he was tachycardic and had a 24 mm Hg blood pressure difference between the left and right arms. Bloods revealed deranged liver function tests and a lymphocytosis. His D-dimer was raised, hence he was treated for presumed pulmonary embolism before imaging was available. Monospot test was positive. He subsequently had both a CT pulmonary angiogram and a CT angiogram of the aorta to exclude pulmonary embolism and aortic dissection. The CT revealed splenomegaly with a large subdiaphragmatic haematoma secondary to splenic rupture. This had likely caused referred pain through diaphragmatic irritation. He was taken to theatre for urgent splenectomy. The unifying diagnosis was infectious mononucleosis complicated by spontaneous splenic rupture secondary to Epstein-Barr virus infection.